SARS-CoV-2 variants of concern dominate in Lahore, Pakistan in April 2021. Issue 11 (30th November 2021) - Sarwar, Muhammad Bilal; Yasir, Muhammad; Alikhan, Nabil-Fareed; Afzal, Nadeem; de Oliveira Martins, Leonardo; Le Viet, Thanh; Trotter, Alexander J.; Prosolek, Sophie J.; Kay, Gemma L.; Foster-Nyarko, Ebenezer; Rudder, Steven; Baker, David J.; et al.
Abstract : The SARS-CoV-2 pandemic continues to expand globally, with case numbers rising in many areas of the world, including the Indian sub-continent. Pakistan has one of the world's largest populations, of over 200 million people and is experiencing a severe third wave of infections caused by SARS-CoV-2 that began in March 2021. In Pakistan, during the third wave until now only 12 SARS-CoV-2 genomes have been collected and among these nine are from Islamabad. This highlights the need for more genome sequencing to allow surveillance of variants in circulation. In fact, more genomes are available among travellers with a travel history from Pakistan, than from within the country itself. We thus aimed to provide a snapshot assessment of circulating lineages in Lahore and surrounding areas with a combined population of 11.1 million. Within a week of April 2021, 102 samples were sequenced. The samples were randomly collected from two hospitals with a diagnostic PCR cutoff value of less than 25 cycles. Analysis of the lineages shows that the Alpha variant of concern (first identified in the UK) dominates, accounting for 97.9 % (97/99) of cases, with the Beta variant of concern (first identified in South Africa) accounting for 2.0 % (2/99) of cases. No other lineages were observed. In depth analysis of the Alpha lineages indicated multiple separate introductions and subsequent establishment within the region. Eight samples were identical to genomes observed in Europe (seven UK, one Switzerland), indicating recent transmission. Genomes of other samples show evidence that these have evolved, indicating sustained transmission over a period of time either within Pakistan or other countries with low-density genome sequencing. Vaccines remain effective against Alpha, however, the low level of Beta against which some vaccines are less effective demonstrates the requirement for continued prospective genomic surveillance.